Phylogenomics of Hemiptera (Insecta: Paraneoptera) based on mitochondrial genomes. (26th November 2012) - CUI, YING; XIE, QIANG; HUA, JIMENG; DANG, KAI; ZHOU, JIANFU; LIU, XIAOGUANG; WANG, GANG; YU, XIN; BU, WENJUN
Abstract : Hemiptera is the largest order in Paraneoptera and the fifth largest in Insecta. Disputes about hemipteran phylogeny have concerned the monophyly of Auchenorrhyncha and relationships between the suborders Fulgoromorpha, Cicadomorpha, Coleorrhyncha and Heteroptera. In a phylogenomic study of Hemiptera, we add two new mitochondrial genomes of Peloridiidae (Coleorrhyncha) to those reported in GenBank, to complete the taxon sampling of all suborders. We used two types of data – amino acid sequences and nucleotides of various combinations between protein coding genes, tRNAs and rRNAs – to infer the phylogeny of Hemiptera. In total 27 taxa of Paraneoptera were sampled, 24 of them being hemipterans. Bayesian inference, maximum likelihood and maximum parsimony analyses were employed. The relationship of Cicadomorpha + Heteroptera is always stable in the results with different combinations between data types and phylogenetic methods, but our results challenge the monophyly of 'Homoptera' and Auchenorrhyncha. In evaluating the relative contribution of each gene, the phylograms generated by single genes CO1, ND1, ND2, ND4 and ND5, respectively, closely matched the tree yielded by the combined datasets. In light of the taxon‐sampling sensitivity of trees based on mitochondrial genomes, the results need to be tested with further data from nuclear genes.